Expected impact from weak reactions with light nuclei in corecollapse supernova simulations - Fischer T.; Martínez-Pinedo G.; Hempel M.; Huther L.; Röpke G.; Typel S.; Lohs A. (EPJ Web of Conferences, 2016)
We study the role of light nuclear clusters in simulations of core-collapse supernovae. Expressions for the reaction rates are developed for a large selection of charged current absorption and scattering processes with light clusters. Medium modifications are taken into account at the mean-field level. We explore the possible impact on the supernova dynamics and the neutrino signal during the mass accretion phase prior to the possible explosion onset as well as during the subsequent protoneutron star deleptnoization after the explosion onset has been launched.